PSYCHIATRIC MORBIDITY AMONG AFGHAN REFUGEES IN PESHAWAR, PAKISTAN - Naeem, Farooq; Mufti, Khalid A; Ayub, Mohammad; Haroon, Asad; Saifi, Farida; Qureshi, Saima Mahmood; Ihsan, Ali; Chaudry, Haroon Rasheed; Dagarwal, Saif ur Rehman; Kingdon, David (Journal of Ayub Medical College Abbottabad, 2005)
Background: A review of the literature shows that refugees in different parts of the world have high rates of psychological and emotional problems. However, psychiatric morbidity among afghan refugees in Pakistan has been poorly studied. Most of the studies of psychiatric disorders come from western countries. However, these studies may not be representative of the afghan refugees in Pakistan. This study was carried out to measure psychiatric morbidity among a group of Afghan refugees attending a psychiatric clinic in Peshawar, Pakistan. Methods: This is a cross sectional study, to measure prevalence of psychiatric morbidity among the residents of Afghan refugee camps in Peshawar, Pakistan, who attended a psychiatric clinic between November 2003 and February 2004. Data were collected using Mini International neuropsychiatry Interview Schedule (MINI), and a form specifically developed for the study. Results: Nearly 80% of our patients had a diagnosis of Post Traumatic Stress Disorder. Nearly half, (47.9%) reported family history of mental illness, while almost a quarter 923.3%) had a physical disability or long term illness. Only 13.7% (106) had contacted health services prior to seeking help for their psychiatric illness. Conclusions: A high number of patients presenting with PTSD is not an unusual finding when one considers the traumatic experiences faced by the general population of Afghanistan. Only a small number of the patients had been in contact with the health services prior to their contact with the psychiatric service. This study highlights the importance of health education among afghan refugees and to establish the mental health services for them. Keywords: Psychiatric, Morbidity, Refugees